Impact of soiling on IV-curves and efficiency of PV-modules. (February 2015) - Schill, Christian; Brachmann, Stefan; Koehl, Michael
Highlights: Soiling impact on the yield and the IV -curves of PV-modules could be monitored automatically. The effect of partial shading that can lead to hotspots by dust or snow could be observed. Rain-fall restored the power output completely. Abstract: The Fraunhofer ISE is running outdoor testing facilities for the investigation of the long-term durability of components and materials used for solar energy conversion. PV-modules play an important role amongst the test samples. The performance of the modules over time is assessed by monitoring the characteristic IV -curve every 10 min. The electronic set-up of the monitoring system consists of individual electronic loads for each module which is switching into an maximum-power-point-tracking mode between the IV -measurements. Soiling of exposed modules could be observed by accident because of building constructions nearby at one test site located on the Gran Canary island, west of Morocco in the Atlantic Ocean. It was decided not to clean the modules, but to clean the irradiation sensors. The decrease of the power output and the efficiency over time were recorded in order to investigate the soiling effect. The efficiencies dropped to 20% of the initial values within 5 months. A minor rain event in between washed the dust partly away and accumulated it at the lower part of the module. This was reflected by the shape of the IV -curves. The curves showed similar changes as partial shading by partial snow cover as was observed at our alpine test site. Finally, a major rain event cleaned the modules and the efficiency was completely restored.